Endoscopic resection of large anastomotic polyps is safe and effective - Cronin, Oliver; Gupta, Sunil; Gauci, Julia; Whitfield, Anthony; O'Sullivan, Timothy; Abuarisha, Muhammad; Wang, Hunter; Lee, Eric Yong Tat; Williams, Stephen J; Burgess, Nicholas Graeme; Bourke, Michael J. (Endoscopy, 2023)
Background Large (≥20mm) adenomatous anastomotic polyps (LAAPs) are uncommon. Data pertaining to their prevalence, characteristics, and the efficacy of endoscopic resection (ER) are absent. A safe and effective strategy for ER would reduce morbidity and healthcare costs.Methods Large nonpedunculated colorectal polyps of ≥20mm (LNPCPs) referred for ER were prospectively studied. Multiple data points were recorded including anastomotic location, polyp morphology, resection modality, complications, and technical success.Results Over 7 years until November 2022, 2629 lesions were referred. Of these, 10 (0.4%) were LAAPs (median size 35 mm [interquartile range (IQR) 30–40mm]). All LAAPs were removed by piecemeal endoscopic mucosal resection (EMR), most (n=9; 90%) in combination with cold-forceps avulsion with adjuvant snare-tip soft coagulation (CAST). On comparison of the LAAP group with the conventional LNPCP group, CAST was more commonly used (90% vs. 9%; P<0.001) and deep mural injury (DMI) type II was more frequent (40% vs. 11%, P=0.003); however, significant DMI (III–V) did not occur. At 6 month (IQR 5.25–6 months) surveillance, there was no recurrence in any of the 10 cases. There were no serious adverse events.Conclusions LAAPs present unique challenges owing to their location overlying an anastomosis. Despite these challenges they can be safely and effectively managed endoscopically without recurrence at endoscopic follow-up.